1992
DOI: 10.1016/s1057-7408(08)80056-3
|View full text |Cite
|
Sign up to set email alerts
|

Mood as a Determinant of Postconsumption Product Evaluations: Mood Effects and Their Dependency on the Affective Intensity of the Consumption Experience

Abstract: Can preconsumption mood influence postconsumption evaluations? In this article, we attempt to answer this question; in doing so, we broaden our understanding of both the factors that can influence consumers' evaluations of the consumption experience as well as the role of mood in consumer behavior. The results of an experimental study show that not only can mood influence postconsumption brand attitudes, but that such effects are moderated by the affective intensity of the consumption experience. Mood effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…This coloring effect did not occur, however, when the ad's affective tone was clearly positive. Although mood-congruency effects on evaluation have been considered to be pervasive and robust (e.g., Mayer et al, 1992;Schwarz, 1990), they appear to be sensitive to the affective ambiguity of the target (e.g., Isen & Shalker, 1982;Miniard et al, 1992). This contingency is noteworthy given that many advertisements are not affectively ambiguous.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This coloring effect did not occur, however, when the ad's affective tone was clearly positive. Although mood-congruency effects on evaluation have been considered to be pervasive and robust (e.g., Mayer et al, 1992;Schwarz, 1990), they appear to be sensitive to the affective ambiguity of the target (e.g., Isen & Shalker, 1982;Miniard et al, 1992). This contingency is noteworthy given that many advertisements are not affectively ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Isen and Shalker (1982) observed that the effect of being in a pleasant mood when assessing the pleasantness of slides of local scenes was stronger when the slides were affectively neutral than when the slides were clearly pleasant or unpleasant. Similarly, Miniard, Bhatla, and Sirdeshmukh (1992) observed that the effect of being in a pleasant or unpleasant mood on participants' rating of the taste of a brand of peanut butter was stronger when the brand's actual taste was ambiguous than when it clearly tasted good or bad. Several mechanisms, which are not necessarily mutually exclusive, can explain why moods have less of an effect when the target is affectively unambiguous.…”
Section: Valence Arousal and Ad Evaluation Valence And Coloringmentioning
confidence: 91%
See 2 more Smart Citations
“…When purchasing products and services, people's preferences are influenced by their momentary mood states (Maier et al, 2012;Quartier, et al, 2009). Moreover, mood affects a person's general purchase willingness (Arnold & Reynolds, 2009) and post-purchase product evaluations (Gorn et al, 1993;Miniard et al, 1992). Secondly, insight into mood can help designers seeking to optimise userproduct interactions, as mood influences which products people choose to interact with (Djamasbi & Strong, 2008;Djamasbi et al, 2010), how they want to interact with these products (Wensveen, 2005), which interaction possibilities they explore (Venkatesh & Speier, 1999), and what kinds of information they process during interaction (Zhang & Jansen, 2009).…”
Section: Introductionmentioning
confidence: 99%